Blood flow restriction impairs the inflammatory adaptations of strength training in overweight men: A clinical randomized trial - Da Silva, Igor Martins; Santos, Maeli Andressa; Galvão, Simone Lunelli; Dorneles, Gilson P.; Lira, Fabio Santos [UNESP]; Romão, Pedro R. T.; Peres, Alessandra (Canadian Science Publishing, 2020)
The aim of this study was to evaluate the impact of high-intensity strength training (ST) or low-intensity strength training with bloodflowrestriction (ST-BFR) on monocyte subsets, the expression of C-C chemokine receptor 5 (CCR5), and CD16 on monocytes, and tumor necrosis factor alpha (TNF-α) production of overweight men. Thirty overweight men were randomly assigned to conventional ST or ST-BFR. Both groups performed exercises of knee extension and biceps curl with equal volume (3 sessions/week) over 8 weeks, and the peripheral frequency of monocytes (CD14+CD16−, classical monocytes; CD14+CD16+, intermediate monocytes; CD14−CD16+, nonclassical monocytes), the mean fluorescence intensity (MFI) of CCR5 and CD16 on CD14+ monocytes; and the production of TNF-α by lipopolysaccharide (LPS)-stimulated cells were quantified. Eight weeks of ST increased the frequency of CD14+CD16− monocytes (p = 0.04) and reduced the percentage of CD14−CD16+ (p = 0.02) and the production of TNF-α by LPS-stimulated cells (p = 0.03). The MFI of CD16 on CD14+ monocytes decreased after the ST intervention (p = 0.02). No difference in monocyte subsets, CCR5 or CD16 expression, and TNF-α production were identified after ST-BFR intervention (p > 0.05). The adoption of ST promotes anti-inflammatory effects on monocyte subsets of overweight men, but this effect was lost when BFR was adopted. Novelty • High-intensity strength training reduces the production of TNF-α and the peripheral frequency of CD16+ monocytes in overweight men. • Blood flow restriction method blunts the strength training adaptations on monocyte subsets and pro-inflammatory TNF-α production in overweight men.
Keywords: Cytokines; Exercise immunology; Inflammation; Monocytes; Overweight; Strength exercise; Tumor necrosis factor-alpha; Vascular occlusion